A microchanneled ceramic membrane for highly efficient oxygen separation - Shao, Xin; Dong, Dehua; Parkinson, Gordon; Li, Chun-Zhu (R S C Publications, 2013)
A microchanneled ceramic membrane has been developed for oxygen separation. Numerous parallel microchannels traverse the ceramic membrane with one open end and another end terminating with a thin dense layer. Compared with conventional dense membranes, the new membrane substantially increases oxygen permeation flux by a factor of greater than 5.